BST SEBAGAI ALTERNATIF PENANGANAN MASALAH KELOMPOK MISKIN PADA MASA PANDEMI COVID-19 DI KELURAHAN TAMAMAUNG, KECAMATAN PANAKKUKANG KOTA MAKASSAR - Andi Ainun; Muhammad Iqbal Latief; Andi Haris (Hasanuddin Journal of Sociology, 2021)
ABSTRACT This study aims to find out the implementation and utilization of the BST policy program against the poor groups affected by Covid-19 in Tamamaung Urban Village. This research was conducted out for 2 months and was conducted from February 2021 to Marchl 2021 in Tamamaung Urban Village, Panakkukang Sub-District, Makassar City. This research uses descriptive qualitative research based on case study research with 6 subjects consisting of BST beneficiaries, urban village officials, and BST beneficiary families in Tamamaung Urban Village. Based on the research results, it was found that the implementation of BST in Tamamaung Subdistrict, Panakkukang Subdistrict, was not going well in general, it could be seen from the lack of socialization to the community so that they did not know about the procedure requirements and criteria for the people who received the BST. And data verification was not carried out because, using DTKS data from the Ministry of Social Affairs and the data used were no longer relevant to current conditions, as a result many poor people did not get BST. And also there is no fixed schedule for disbursement which results in the disbursement process not running properly. Meanwhile, the majority of BST utilization uses BST funds for basic needs, school supplies and business capital. Keywords: Social Policy, Cash Social Assistance, Poor Group, Covid-19